Clientelistic parties and satisfaction with democracy. (July 2020) - Wang, Yi-Ting
Using both a cross-national data set on parties' accountability strategies and public opinion survey data, this article provides a systematic analysis of how parties' reliance on clientelistic strategies correlates with citizen evaluations of regime performance. Our analyses suggest that in systems where parties in general rely more heavily on clientelism, principles of democratic equality are undermined, and citizens on average express a lower level of satisfaction. In addition to democratic norms, material benefits are also closely related to citizens' regime evaluations. Within countries, supporters of parties that make substantial clientelistic efforts are more satisfied than other citizens, because they are likely to be beneficiaries of this accountability mode. This within-country gap between clientelistic and non-clientelistic parties' supporters widens where the clientelistic parties deliver benefits more effectively and in countries with lower overall democratic quality.